Analisis Perbandingan Kinerja Keuangan Bank Sebelum Dan Sesudah Merger Diukur Pada Aspek Profitabilitas Pada PT. Bank Syariah Indonesia Tbk. - Mustikawati Annisa; Tenri Sayu Puspitaningsih Dipoatmodjo; Nurman Nurman; Amiruddin Tawe; Anwar Anwar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The progress of Islamic banking in Indonesia led to the merger of three Islamic banks, namely Bank Mandiri Syariah, Bank BNI Syariah, and Bank BRI Syariah became PT. Bank Syariah Indonesia. Financial performance is expected to improve compared to before, indicating the success of the merger. This study aims to determine the difference in financial performance using a comparative analysis of the profitability ratio of state-owned Islamic banks before the merger in 2019-2020 and after merging into PT. Bank Syariah Indonesia Tbk. for 2021-2022 by measuring the level of ROA, ROE, and BOPO ratios in each bank. Data collection is used using documentation techniques. Data analysis was carried out using paired T-tests to determine there were significant differences before and after the merger. The results showed that there was a significant increase in each ratio after the merger. This indicates that there is an increase in financial performance after the merger.